If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + 1x = 0 Solving 7 + 1x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 1x = 0 + -7 Combine like terms: 7 + -7 = 0 0 + 1x = 0 + -7 1x = 0 + -7 Combine like terms: 0 + -7 = -7 1x = -7 Divide each side by '1'. x = -7 Simplifying x = -7
| 10x^2-21x-21=0 | | (6/1)=(3/4)b | | 8a+4=2a+4 | | 10(2a-3b)-1(4b-2a)= | | 19-4+5-16= | | 3-8x-16x^4=0 | | (3x/4)=2 | | 3x+5yi=8-i | | f(x)=tan(cos(2x)) | | (5x/6)=0 | | 5/3x=2/3x+1/3 | | -1/8z=-5.5 | | x+14=171 | | (-3/5)m=12 | | hj-2h+5g+4f-20= | | 3y-4=6 | | -16x^2-7x+10=0 | | 2.38=48 | | -16x^2-7x-1=0 | | 5(2w+3)10w=6(4w+1) | | 4+-2v+12=-8 | | x^2-36/2x-12 | | 2(1+3s)-4=6s-2 | | d=3m | | 6+3+2+2= | | (-b/3)=6 | | 5-(f+3)=5f | | 91=-4(6-6b)-5 | | 2ln(x)=ln(21) | | 17=32 | | 40=16t^2+88t | | 20=(1/4c) |